2020
DOI: 10.1002/ejhf.1732
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy stimulation and intracellular sodium reduction as mediators of the cardioprotective effect of sodium–glucose cotransporter 2 inhibitors

Abstract: In five large-scale trials involving >40 000 patients, sodium-glucose cotransporter 2 (SGLT2) inhibitors decreased the risk of serious heart failure events by 25-40%. This effect cannot be explained by control of hyperglycaemia, since it is not observed with antidiabetic drugs with greater glucose-lowering effects. It cannot be attributed to ketogenesis, since it is not causally linked to ketone body production, and the benefit is not enhanced in patients with diabetes. The effect cannot be ascribed to a natri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 182 publications
(423 reference statements)
2
80
0
1
Order By: Relevance
“…Our previous research proved that the increase of autophagy level helped to restore cardiac function and alleviate cardiac remodeling under hypoxic injury conditions (Hu et al, 2016). On the contrary, if the level of autophagy cannot be increased correspondingly after suffering the injury, it will lead to further deterioration of heart function (Hu et al, 2016;Packer, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Our previous research proved that the increase of autophagy level helped to restore cardiac function and alleviate cardiac remodeling under hypoxic injury conditions (Hu et al, 2016). On the contrary, if the level of autophagy cannot be increased correspondingly after suffering the injury, it will lead to further deterioration of heart function (Hu et al, 2016;Packer, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…For example, it is known that metformin stimulates autophagy via activating AMPK and sirtuin-1 (SIRT1) and by this way, may contribute to the cardioprotective effects seen in experimental models of HF (Gundewar et al, 2009). Recent studies revealed that SGLT2i may exert cardioprotective effects by stimulating autophagy (Levine et al, 2015), which may involve the activation of AMPK and SIRT1 (Packer, 2020). The overlap in the mechanism of action between metformin and SGLT2i may be the reason for the reduced cardioprotective effects of SGLT2i in patients with metformin treatment at baseline, when compared to the non-metformin group (Packer, 2020).…”
Section: Mechanisms Of Cardioprotection Of the Antidiabetic Drugsmentioning
confidence: 99%
“…Recent studies revealed that SGLT2i may exert cardioprotective effects by stimulating autophagy (Levine et al, 2015), which may involve the activation of AMPK and SIRT1 (Packer, 2020). The overlap in the mechanism of action between metformin and SGLT2i may be the reason for the reduced cardioprotective effects of SGLT2i in patients with metformin treatment at baseline, when compared to the non-metformin group (Packer, 2020).…”
Section: Mechanisms Of Cardioprotection Of the Antidiabetic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, they cannot be ascribed to natriuretic effect, since diuretic therapy has been associated with increased risk of CVD and mortality in patients with HF. [13][14][15][16] As a consequence, accumulating evidence has been gathered in an attempt to figure out the possible underlying mechanisms of cardioprotection. In view of the rapid decline in risk of HHF, it can be speculated that the benefits of SGLT2Is are due to the direct effects on the heart itself, namely improved DCM, instead of metabolic improvement.…”
Section: Introductionmentioning
confidence: 99%